Quantification of gallium cryo-FIB milling damage in biological lamellae - Bronwyn A. Lucas; Nikolaus Grigorieff (2023)
Cryogenic electron microscopy (cryo-EM) can reveal the molecular details of biological processes in their native, cellular environment at atomic resolution. However, few cells are sufficiently thin to permit imaging with cryo-EM. Thinning of frozen cells to <500 nm lamellae by focused-ion-beam (FIB) milling has enabled visualization of cellular structures with cryo-EM. FIB milling represents a significant advance over prior approaches because of its ease of use, scalability, and lack of large-scale sample distortions. However, the amount of damage it causes to a thinned cell section has not yet been determined. We recently described an approach for detecting and identifying single molecules in cryo-EM images of cells using 2D template matching (2DTM). 2DTM is sensitive to small differences between a molecular model (template) and the detected structure (target). Here, we use 2DTM to demonstrate that under the standard conditions used for machining lamellae of biological samples, FIB milling introduces a layer of variable damage that extends to a depth of 60 nm from each lamella surface. This layer of damage limits the recovery of information for in situ structural biology. We find that the mechanism of FIB milling damage is distinct from radiation damage during cryo-EM imaging. By accounting for both electron scattering and FIB milling damage, we estimate that FIB milling damage with current protocols will negate the potential improvements from lamella thinning beyond 90 nm.